Preterm-Born Young Women Have Weaker Hand Grip Strength Compared to Their Full-Term-Born Peers - Ella Bruun; Pauli Pätsi; Markku Leskinen; Krista Björkman; Petri Kulmala; Mikko P. Tulppo; Marita Valkama; Marja Ojaniemi (MDPI AG, 2023)
Prematurity has been linked to lower muscular fitness and increased morbidity across the human lifespan. Hand grip strength is widely used as a measure of muscle strength. Previous studies have shown inconsistent results regarding the role of vitamin D in hand grip strength. Here, we investigated hand grip strength and the effects of a yearlong vitamin D supplementation in healthy preterm-born young adults. We recruited 38 young adults born preterm at either ≤32 weeks' gestation or <34 weeks' gestation and weighing <1500 g, as well as 39 gender- and age-matched controls, for this study. Anthropometric measurements, hand grip strengths, and vitamin D concentrations were recorded. These investigations were repeated after a yearlong vitamin D supplementation intervention. There was a significant difference in the age- and gender-specific hand grip strength ranks between the preterm- and full-term-born young adults: 57.9% and 30.7%, respectively, were below average (p = 0.009). In the preterm-born group, the females had significantly lower hand grip strengths compared to their full-term-born peers, with a mean difference of −3.46 kg (95% CI: −6.68 to −0.247; p = 0.035). In a linear regression analysis, the preterm-born female adult height was negatively associated with hand grip strength (R2 = 0.24, F (1.43) = 13.61, p < 0.001). The vitamin D concentrations were increased after the supplementation period, with no association with hand grip strength. According to our results, preterm-born young females are at risk for lower muscle strength, independent of their current vitamin D status.